Dimethyl Fumarate Ameliorates Acute Pancreatitis in Rodent. Issue 3 (April 2015) - Robles, Lourdes; Vaziri, Nosratola D.; Li, Shiri; Takasu, Chie; Masuda, Yuichi; Vo, Kelly; Farzaneh, Seyed H.; Stamos, Micheal J.; Ichii, Hirohito
<x xml:space="preserve">Abstract</x> Objectives Pancreatitis is a complex inflammatory disorder, ranging from a mild attack, to severe and potentially fatal condition. Dimethyl fumarate (DMF), a potent antioxidant and anti-inflammatory, has been used medicinally for decades. The purpose of this study was to test the hypothesis that treatment with DMF may ameliorate acute pancreatitis (AP) in a rodent model. Methods Rats were treated with DMF (25 mg/kg) 24 hours prior to AP induction with l-arginine (3 g/kg). At 72 hours, the pancreas was processed for histology. Serum amylase, lactate dehydrogenase, pancreatic trypsin, and lipid peroxidation product (malondialdehyde) were evaluated. Key cytokines and chemokines in the supernatant of lipopolysaccharide-stimulated splenocytes were also determined. Results Pancreata from DMF-treated rats showed reductions in the severity of inflammatory cell infiltration, acinar damage, perilobar edema, and cell necrosis. This was associated with significantly lower amylase and malondialdehyde but not lactate dehydrogenase or trypsin levels. The apoptotic pancreatic cells (cleaved caspase 3 positive) were significantly lower in the DMF-treated rats. Lipopolysaccharide-stimulated splenocytes treated with DMF produced a significantly lower amount of key inflammatory mediators. Conclusion Administration of DMF attenuates AP in rats.